2014
DOI: 10.1017/s0954422414000213
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre and the importance of the gut microbiota in feline nutrition: a review

Abstract: Domestic cats are obligate carnivores and in this light hindgut fermentation has been considered unimportant in this species. However, a diverse microbiota has been found in the small and large intestines of domestic cats. Additionally, in vitro and in vivo studies support the hypothesis that microbial fermentation is significant in felines with potential benefits to the host. Results on microbiota composition and microbial counts in different regions of the feline gastrointestinal tract are compiled, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 94 publications
(221 reference statements)
2
30
0
1
Order By: Relevance
“…Studies have shown an effect of these ingredients on fecal microbial composition, nutrient digestibility, and short-chain fatty acid concentrations, particularly in dogs (Patra, 2011; Schmitz & Suchodolski, 2016; De Godoy, Kerr & Fahey, 2013). Domestic cats are obligate carnivores but several studies support the hypothesis that microbial fermentation inside the distal gut is significant and beneficial to the host (Rochus, Janssens & Hesta, 2014). However, most of the published studies have researched the effect of natural prebiotics (with and without processing, e.g.,聽potato fiber, see Panasevich et al, 2015) as opposed to commercial preparations containing these ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown an effect of these ingredients on fecal microbial composition, nutrient digestibility, and short-chain fatty acid concentrations, particularly in dogs (Patra, 2011; Schmitz & Suchodolski, 2016; De Godoy, Kerr & Fahey, 2013). Domestic cats are obligate carnivores but several studies support the hypothesis that microbial fermentation inside the distal gut is significant and beneficial to the host (Rochus, Janssens & Hesta, 2014). However, most of the published studies have researched the effect of natural prebiotics (with and without processing, e.g.,聽potato fiber, see Panasevich et al, 2015) as opposed to commercial preparations containing these ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Miscellaneous: Changes in the gut microbiota as a function of diet have also been shown in many other animals, including dogs [33], cats [34], chickens [35], pigs [36], seals [37], howler monkeys [38] and frogs [39]. In those animals that have been examined, compositional changes in the gut microbiome have also been correlated with overall changes in physiology.…”
Section: Introduction: the Hologenome Conceptmentioning
confidence: 97%
“…Diet is recognized as one of the major factors driving the composition and metabolism of the gut microbiota (Russell et al 2013). While many studies have highlighted the beneficial effects deriving from the dietary inclusion of non-digestible carbohydrates and prebiotics in dogs and cats (Pinna and Biagi 2014;Rochus et al 2014), little is known about feeding functional food components to these animals.…”
Section: Introductionmentioning
confidence: 99%